2013
DOI: 10.1111/joie.12018
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of Auctions with Buy‐It‐Now: Theory and Evidence

Abstract: In the ascending‐price auctions with Yahoo!‐type buy‐it‐now (BIN), we characterize and derive the closed‐form solution for the optimal bidding strategy of the bidders and the optimal BIN price of the seller when they are both risk‐averse. The seller is shown to be strictly better off with the BIN option, while the bidders are better off only when their valuation is high enough. The theory also implies that the expected transaction price is higher in an auction with an optimal BIN price than one without a BIN o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Finally, the pure auction sellers had the largest average number of items during the period of our study (20), which was not substantially greater than that for the fixed-price auction sellers (16). But the BIN auction sellers had far fewer items than the other two (6). This suggests that the number of listings had a certain relationship with a seller's incentive to adopt BIN.…”
Section: Data Descriptionmentioning
confidence: 64%
See 3 more Smart Citations
“…Finally, the pure auction sellers had the largest average number of items during the period of our study (20), which was not substantially greater than that for the fixed-price auction sellers (16). But the BIN auction sellers had far fewer items than the other two (6). This suggests that the number of listings had a certain relationship with a seller's incentive to adopt BIN.…”
Section: Data Descriptionmentioning
confidence: 64%
“…This is not the case: In our sample the correlation between reputation and experience is only 0.05. 16 For example, Chen et al (2011) has shown that BIN benefits the seller if and only if either the seller or the bidder is risk-averse. 17 Also note that eBay charges sellers who list more than 50 items per month for using BIN.…”
Section: Empirical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the above papers, there has also been work that compares the use of auctions with the use of posted prices in a variety of settings (Hammond, 2010(Hammond, , 2013Julien et al, 2002;Kultti, 1999;Wang, 1993Wang, , 1998Vakrat and Seidmann, 1999;van Ryzin and Vulcano, 2004;Vulcano et al, 2002;Zeithammer and Liu, 2008), work on optimal selling mechanisms when buyers arrive dynamically (Board and Skrzypacz, 2014;Vulcano et al, 2002), and work on models of eBay auctions and related markets (Ackerberg et al, 2006;Ambrus et al, 2014;Bajari and Hortaçsu, 2003;Chen et al, 2013;Hidvegi et al, 2006;Peters and Severinov, 2006;Ockenfels and Roth, 2006;Roth and Ockenfels, 2002). Finally, there has also been work on sequential search mechanisms when it is costly for buyers and sellers to interact that illustrates that it can be optimal to first see if there is an agent willing to complete a transaction at a particular price and then complete the transaction with the agent willing to accept the most favorable price possible if no agent accepted the initial offer (Ehrman and Peters, 1994;McAfee and McMillan, 1988).…”
Section: Introductionmentioning
confidence: 97%